2022
DOI: 10.1039/d2ra01249a
|View full text |Cite
|
Sign up to set email alerts
|

Study on SO2 and Cl2 sensor application of 2D PbSe based on first principles calculations

Abstract: In this paper, we use 2D PbSe to design a gas sensor to monitor the presence of SO2 and Cl2. The first principle calculation shows that our scheme is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…An effective twodimensional Coulomb potential was proposed, which was used to describe the lateral motion of charge carriers and calculate corrections to the solutions of the Schrodinger equation for motion perpendicular to the interfaces. The authors state that their calculations agree well with the experimental data; however, they used data for NSs with a thickness Several approaches are used for the theoretical description of the electronic subsystem energy spectrum and the optical properties of quasi-2D semiconductor nanostructures of lead chalcogenides: the k•p perturbation theory effective mass method [55][56][57], the tight-binding method [53], and density functional theory (DFT) [29,37,46,51,54,58]. Each of them has its advantages and disadvantages.…”
Section: Optical Propertiesmentioning
confidence: 86%
See 1 more Smart Citation
“…An effective twodimensional Coulomb potential was proposed, which was used to describe the lateral motion of charge carriers and calculate corrections to the solutions of the Schrodinger equation for motion perpendicular to the interfaces. The authors state that their calculations agree well with the experimental data; however, they used data for NSs with a thickness Several approaches are used for the theoretical description of the electronic subsystem energy spectrum and the optical properties of quasi-2D semiconductor nanostructures of lead chalcogenides: the k•p perturbation theory effective mass method [55][56][57], the tight-binding method [53], and density functional theory (DFT) [29,37,46,51,54,58]. Each of them has its advantages and disadvantages.…”
Section: Optical Propertiesmentioning
confidence: 86%
“…Scheme 1 shows a qualitative transformation of a PbX nanomaterial's energy structure due to the transition from one-dimensional to three-dimensional confinement. Several approaches are used for the theoretical description of the electronic subsystem energy spectrum and the optical properties of quasi-2D semiconductor nanostructures of lead chalcogenides: the k•p perturbation theory effective mass method [55][56][57], the tight-binding method [53], and density functional theory (DFT) [29,37,46,51,54,58]. Each of them has its advantages and disadvantages.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Similar research about adsorption in two-dimensional material can be also found. 44 On the surfaces of V O -Al and the aggregation must be maintained at a reasonable level to reduce the adsorption energy of OH.…”
Section: T H Imentioning
confidence: 99%
“…An overly high or overly low Bader charge will impede the adsorption of OH*. Similar research about adsorption in two-dimensional material can be also found …”
mentioning
confidence: 99%
“…After that, several scientists worldwide have begun to examine the development of new gas sensors, including those using silicon semiconductors and solid electrolytes. Various kinds of sensor materials, including MOS (metal oxide semiconductors), sulfides, binary lead chalcogenide nanomaterials, MOFs (metal-organic frameworks), van der Waals heterostructures, noble metals-based composites, have also been intensively published on other papers with their own advantages and disadvantages [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%